The Political Aspects of the Establishment of the Planning and Budgeting Policy for The Directorate of Occupational and Sports Health of the Ministry of Health - Ramadhan, Ben Fauzi; Thabrany, Hasbullah; Ayuningtyas, Dumilah (UI Scholars Hub, 2017)
The process to establish a planning and budgeting policy in the Directorate for Occupational and Sports Health is very dynamic and it fluctuates according to the goals and priorities of the policy. This research aims to ascertain how far the political aspects influences the establishment process. This research was a qualitative research accomllished through in-depth interviews with related parties. The framework used the planning and budgeting systems model and process/cycle. Results of this research indicated that politics played a major role in the policy establishment process in conflicts, cooperation, and negotiations when setting the size and allocation of the budget and the targets aimed. The main points in the process are the priorities of the program, the fiscal capacity of the nation, and the results of the previous year’s evaluation. We recommend that the human resources of the directorate are equipped abilities to advocate the importance of the occupational and sports health program.